A toothless bonobo skull challenges the notion of alternative subsistence strategies in early Homo. Issue 147 (October 2020) - Surbeck, Martin
Highlights: The toothless bonobo is surviving in the wild without the help of other individuals and without soft domesticated fruits. Inspection of skeletal remains challenges inferences from fossil records about potential pro-sociality among early humans.